2016
DOI: 10.13177/irpa.a.2016.12.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism among Icelandic Mayors: Job Postings, Experience and Education as Determinants of Professionalism at the Icelandic Local Level

Abstract: Professionalism is thought to be synonymous with good governance, a vital component of a modern and efficient local government. Traditionally, top managers, such as American city managers, are seen as the archetype of professionalism, while municipalities ruled by executive mayors have been judged to be less professional. In Iceland, mayors are recruited largely through two processes: through hiring following nationwide job postings (managermayors) and through political appointment from within the municipal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One of the main measurements on administrative capacity is the local governments capacity to hire professional and specialised staff into the town hall (Kjaer and Mouritzen 2003;Lundtorp 2000). Previous studies have shown that Icelandic local authorities stress professional capacity and skills when hiring manager-mayors (Hlynsdóttir 2016b), less is known about the overall capacity of the local administrative level. In his 2001 study on Icelandic local government, Gunnar Helgi Kristinsson pointed out that size was a crucial factor in defining the structure of local administration.…”
Section: The Number Of Staff In Town Hallsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main measurements on administrative capacity is the local governments capacity to hire professional and specialised staff into the town hall (Kjaer and Mouritzen 2003;Lundtorp 2000). Previous studies have shown that Icelandic local authorities stress professional capacity and skills when hiring manager-mayors (Hlynsdóttir 2016b), less is known about the overall capacity of the local administrative level. In his 2001 study on Icelandic local government, Gunnar Helgi Kristinsson pointed out that size was a crucial factor in defining the structure of local administration.…”
Section: The Number Of Staff In Town Hallsmentioning
confidence: 99%
“…The first type is an individual who is also a member of the council (political mayor) and the second type is an individual who is not a member of the council (manager-mayor). Both types of chief executive play central roles and often possess considerable political and professional capacity (Hlynsdóttir 2016b).…”
Section: Stjórnmál and Stjórnsýslamentioning
confidence: 99%
See 1 more Smart Citation
“…Most local authorities have a relatively small local administration; and the council plays an important role in the process of task implementation alongside the municipal manager. Therefore, a high level of turnover in the council, combined with a high level of turnover among municipal administrators (Hlynsdóttir 2016c) and a small administration, poses a threat to the overall performance of the local level of government.…”
Section: Stjórnmál and Stjórnsýslamentioning
confidence: 99%